'A prospective case control study to evaluate shock index for identifying patients at risk of clinically important malaria in refugee settings'. (April 2023) - Kuhrt, Katy; Seed, Paul T; Shennan, Andrew H
Bidibidi Refugee Settlement's 223, 000 refugees are vulnerable to malaria due to crowded conditions and limited healthcare access. Early identification and referral of suspected cases is key to reduce morbidity and mortality. We evaluated the shock index (heart rate/ systolic blood pressure) for detection of abnormal vital signs, calculated by the CRADLE Vital Signs Alert device, which can be used in routine patient blood pressure and heart rate assessment by non-medically trained Voluntary Health Team workers. The single most frequent diagnosis causing shock was malaria, and thus the device was useful to detect severe cases (as well as discovering other cases), after calculating appropriate shock indices.